Author's response. Issue 3 (2nd July 2016) - Nikiforov, Igor V.
ABSTRACT: This article contains the author's responses to the five discussion papers commenting on the results presented in Nikiforov (2016 ). The quickest detection/isolation of abrupt changes is the generalization of the quickest detection of abrupt changes to the case of M post-change hypotheses. It is necessary to detect the change in distribution as soon as possible and to indicate which hypothesis is true after a change occurs.